The role of religious education in shaping religious moderation awareness among students - Edi Ahyani (12 Waiheru, 2024)
Religious education in higher education institutions plays a central role in shaping attitudes and awareness of religious moderation among students. This study aims to investigate the impact of mastery of religious education materials on the understanding of religious moderation and the role of teachers in shaping student perspectives. The research method uses a qualitative approach with interview techniques and content analysis. The research method uses a qualitative approach with interview techniques and content analysis. The research sample involved IAIN Ambon students from various study programs who participated in religious education courses with a total of 15 respondents. The results showed that religious education has a positive influence in shaping the awareness of religious moderation, especially through a deep understanding of the values of diversity and interfaith dialogue. The importance of teachers' role in supporting the learning process is evident in their ability to create a classroom environment that is open to diverse discussion and understanding. In addition, the study provides insight into teaching strategies that are effective in facilitating the development of attitudes toward religious moderation. The findings of this study have practical implications for the development of religious education curricula in universities, emphasizing the need for the integration of religious moderation values in every aspect of learning. As such, this research contributes to our understanding of how religious education can be a positive force in shaping attitudes toward religious moderation among college students.